A Seniors' perspective on social networks, perceived stress and quality of life - Sónia Ferreira; Francisco Regalado; Ana Veloso (Instituto Politécnico de Viseu, 2022)
Introduction: The study of initiatives that promote active ageing is crucial given the global population demography. Objetive: To study the social support networks, stress, and quality of life of participants in the SEDUCE 2.0 project. Methods: Cross-sectional descriptive research, quantitative and qualitative. Data were collected through: Questionnaire Survey for participants' characterization; Portuguese versions of the constructs Lubben's Brief Social Network Scale; Perceived Stress Scale; WHOQOL-BREF; and a logbook to record the co-design sessions for miOne community development. The study included 31 participants from two Universities of The Third Age, aged between 56 and 86 years (M= 69.90; SD=7.04). Results: Participants revealed a relevant social support network. The network with whom they feel close enough to call and ask for help, and to talk about personal matters is smaller. The analysis of perceived stress reveals positive results, apart from who felt worried/nervous/stressed. All items of the perceived stress analysis showed positive results, except when a higher percentage reported feeling worried/nervous/stressed. Participants showed a good perception towards all items of the quality of life scale, except for the last question where they reported that they sometimes perceived negative feelings. Conclusion: The participants show a good social support network, good quality of life and low stress levels. The results cannot begeneralised, but it leaves interesting and relevant clues about the older population.